Back to school : first year university experiences of mature Māori women : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Educational Psychology at Massey University, Albany, New Zealand - Fitzpatrick, Megan Lee (Massey University, 2015)
This thesis is an exploration of the first year experiences of five Maori women who attended a tertiary institution in Aotearoa as mature students. Situated in the context of higher education and student life, their first year experiences includes challenges related to childhood school experiences, language and culture clashes. The importance of collectivist Maori values as a form of Maori identification supports them through their academic journeys. Interviews with five mature Maori women revealed the conflict and cultural dissonance between western University values and Maori cultural values that impacted on their first years of study. It was also clear that Maori values such as whanau and whanaungatanga were critical to providing cultural support for these women. Findings also show that for these Maori women the practice of Maori values contributes to their identity as Maori women and also to the wellbeing of their whanau, hapu and iwi. These stories explore how the mature Maori women in this study, overcame the very powerful influence of negative experience as children within the state education systems, to begin tertiary study later in life.
Keywords: Women, Maori; College freshmen; Education (Higher); New Zealand